(untitled) (Journal of actual problems of jurisprudence, 2019)
All accentuation considered temporary change in the nature, to smooth when growing up. At the same time, many of them go into mental illness, or stored for life. Accentuation are though extreme, but are normal. Therefore, the «accentuation of character» can not be a psychiatric diagnosis. Keywords: genesis, accentuation, minors, offense, rule of law, character, pathology.